Usos da Provinha Brasil por professores de uma escola municipal da cidade de São Paulo - Scalzaretto, Roberta Estevão Cassará (2017)
The present research had the goal to identify the uses 2nd Grade Elementary School teachers from a municipal school in São Paulo make from results obtained from the correction of Provinha Brasil de Leitura. In order to reach such goals, one decided to make use of the case study among types of qualitative research and, as a data collection tool, the observation and semi-structured interview. The theoretical approach about educational evaluation used to support the investigation and strengthen the data analysis was based on Domingos Fernandes (2009), Lukas Mujica and Santiago Etxeberría (2009), Depresbiteris and Tavares (2009), Gatti (2003) and Sousa (2010). Results indicate that Provinha Brasil is recognised as an important tool used to collaborate in teachers’ educational practice who have participated on this study and that, despite of its use, they do not totally encompass the goals of this evaluation. It was also possible to observe the relation between the way in which teachers use its results and the perception they have about the educational evaluation once that judgements from the collected data still show some deadlocks in the dialogue with educational aspects